Pengembangan Media Pembelajaran Interaktif pada Materi Sistem Endokrin untuk Meningkatkan Motivasi Belajar Siswa Kelas XI SMA - Tutik Utika Sari; Tien Aminatun (Postgraduate, University of Mataram, 2024)
This research aims to produce interactive learning media that is feasible, practical and effective to use on endocrine system material to increase learning motivation for class XI high school students. This research uses the method Research and Development (R&D) with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The research was conducted at SMA Negeri 1 Minggir on class XI MIPA students consisting of 2 classes, namely the control class and the experimental class with a total of 36 students each. The data collection instruments used were material expert and media expert validation sheets, biology teacher assessment sheets, student response sheets and non-test instruments in the form of questionnaires. Analysis of learning motivation data was calculated using the independent sample t˗test with a significance level of 0.05. The average learning motivation obtained in the experimental class was 89.98 with an N-gain value of 0.75 in the high category, while the average learning motivation in the control class was 59.72 with an N-gain value of 0.55, in the medium category. Based on the results of the Independent Sample t-test, the results obtained were 0.000 < 0.05 and it was stated that media use interactive learning proven effective in increasing student learning motivation.